Changes in water and chlorophyll fluorescence parameters under osmotic stress in wheat cultivars - Gallé, Ágnes (Acta Biologica Szegediensis, 2002)
Drought tolerant wheat cultivars exposed to low water potential can be characterized by growth response, stomatal conductance of leaves, by changes in water relations and ion accumulation of tissues and by fluorescence induction parameters under water stress. Two strategies of acclimation to drought stress have been found: plants using the first strategy save tissue water content by a fast decrease of stomatal conductance, maintain pressure potential and photosynthetic activity of leaves. In the second group the closure of stomata occurs later resulting in an intensive loss of water and a fast decrease of water potential in the leaves and tissues restore their turgor after a relatively long acclimation phase.